Running stride peak forces inversely determine running economy in elite runners - Storen, O.; Helgerud, J.; Hoff, J. (The Journal of Strength and Conditioning Research, 2011)
The present study investigated the relationship between running economy (RE) at 15 km/h, 3.000-m race time, maximal strength, and a number of physiological, anthropometrical, and mechanical variables. The variables measured included RE, maximal oxygen consumption, heart rate, step length and frequency, contact time, and the peak horizontal and vertical forces of each step. Maximal strength was measured as the 1 repetition maximum (1RM) half-squat using a leg press machine. Eleven male elite endurance athletes with a VO2max of 75.8 ± 6.2 mL/kgmin participated in this study. After the anthropometric data were collected, they were tested for RE, running characteristics, and force measures on a level treadmill at 15 km/h. The athletes wore contact soles, and the treadmill was placed on a force platform. Maximal oxygen consumption and 1RM were tested after the RE measurements. The sum of horizontal and vertical peak forces revealed a significant inverse correlation (p < 0.05) both with 3,000-m performance (R = 0.71) and RE (R = 0.66). Inverse correlations were also found (p < 0.05) between RE and body height (R = 0.61) and between RE and body fat percentage (R = 0.62). In conclusion, the sum of horizontal and vertical peak forces was found to be negatively correlated to running economy and 3,000-m running performance, indicating that avoiding vertical movements and high horizontal braking force is crucial for a positive development of RE.